Land Governance: Traditions, Experience and Modern Development - Sharyi, Grygorii; Tymoshevskyi, Vladyslav; Yurko, Ilona; Tymoshevska, Tetyana (International Journal of Engineering and Technology, 2018)
The land governance system development, main directions in the part of land relations institutionalization and land evaluation works realization are considered in the article. Reforming land relations based on the land private ownership institution, aiming to become an ideal efficient land owner, in a number of industries received the opposite result. Market transformations were ahead and will be ahead of institutional changes in Ukraine, science and law-making lag in the real economic situation in the land use organization system. Studying domestic historical and foreign experience, the authors found a close relationship between the institutional provision of land relations and economic, agrarian-industrial, social, administrative-territorial and demographic reforms parameters and their final results. There was a lack of focus organization of economically feasible and environmentally safe land use. Authors determined that the land relations institutional development, - subject to the institutional economy laws, - is defined as development, taking into account not only economic criteria and legal norms set, but also ones informally recorded in ordinary law, customs and traditions and spontaneously defined boundaries that structure the interaction of individuals in the land relations field, considering not only economic but also society's political, religious and social development aspects.Â Â